PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM TRANSFORMASI DIGITAL PELAYANAN KESEHATAN MELALUI IMPLEMENTASI REKAM MEDIS ELEKTRONIK PADA PELAYANAN RAWAT JALAN - Azzahra Lailatul Basir; kikiKiki Riezki Yudistiani; Moch Djati Rusyana; Sophia Restantini; Nurhaeni Sikki (Bajang Institute, 2026)
The digital transformation of health services in Indonesia is being accelerated by the Indonesian Ministry of Health Regulation No. 24 of 2022, which requires all health facilities to implement Electronic Medical Records (EMR). The success of EMR implementation is not solely determined by technological readiness, but largely depends on the quality of Human Resource Management (HRM), which is at the forefront of implementation, particularly in outpatient units. This systematic review aims to analyze the role of HRM in supporting the digital transformation of health services through EMR implementation in outpatient services in Indonesia, identify the barriers encountered, and formulate recommended strategies. This study used a systematic review design with a qualitative approach through a literature search on Google Scholar, Portal Garuda, and SINTA for publications from 2021–2025. Inclusion criteria included Indonesian-language articles discussing EMR implementation and/or HRM in Indonesian health facilities, published in indexed journals. Five articles met the criteria and were analyzed using a thematic synthesis approach. The review shows that HRM plays a crucial role in the success of outpatient EMR implementation through four main dimensions: training and digital competency development, leadership and organizational culture, healthcare worker readiness and resistance, and governance and workload management. Consistently identified HRM barriers include low digital competency among healthcare workers, resistance to change, system–workflow misalignment, and a lack of structured training. Effective HRM, integrated with digital transformation strategy, is a key prerequisite for the successful implementation of EMR in outpatient services. A systematic change management approach, continuous training programs, and transformational leadership are needed to optimize EMR adoption.